Isolasi Senyawa Kimia Utama Dari Fraksi Aktif Sitotoksik Spon Laut Petrosia sp (MN05) - Dian Handayani; Corry Handayani; Krisyanella Krisyanella (STIFARM Padang, 2012)
Isolation of major compound (CH-05-SP) from cytotoxic fraction of marine sponge Petrosia sp (MN 05) using maceration, fractionation, column chromatography and recrystallization methods has been conducted. The result of physical and chemical analysis showed that the isolated compound was white crystal, melted at 180º-183ºC and including as terpenoid.